The Effect of Emotional Intelligence and Learning Motivation on Accounting Understanding with Lecturer Competency as Moderating Variables (Case Study on Accounting Study Program Alumni) - Lidya Kartika Dhewi; Nurul Hidayah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aimed to examine the effect of emotional intelligence and learning motivation on accounting understanding through lecturer competence as a moderating variable. This research is quantitative research with primary data in a questionnaire. The sample is a non-probability sampling method with 100 alumni respondents from several universities. Technical data analysis using Partial Least Square. The results showed that emotional intelligence and learning motivation had a significant positive effect on accounting understanding. In contrast, emotional intelligence and learning motivation through lecturer competence did not affect accounting understanding. Through the results of this study, it is hoped that universities have an essential role in increasing students' knowledge of accounting to produce quality graduates. This research is essential in the world of education, especially universities, which of course want graduates with the best quality, and so that students, when they graduate, can compete in the world of work.